Prevalence of Reduced Vision among UK Elderly Drivers: The Bridlington Eye Assessment Project (BEAP)—A Cross-Sectional Study. (15th September 2022) - Wilde, Craig; Poostchi, Ali; Panos, Georgios D.; Hillman, Jonathan G.; MacNab, Hamish K.; Dua, Harminder; Amoaku, Winfried M.; Vernon, Stephen A.
Abstract : Self-assessment of driving fitness is mandatory in the United Kingdom. A paucity of data on visual function among drivers exists. We report prevalence of elderly drivers below legal visual acuity (VA) standard from a population study (The Bridlington Eye Assessment Project (BEAP)) conducted from 2002 to 2006. All residents aged ≥65 years were invited, 3459 undergoing structured interviews/ophthalmic examinations. Driving status was recorded, VA measured, and visual field (VF) testing performed. Outcomes were prevalence and characteristics of drivers below VA legal standard and prevalence of bilateral VF defects. Conditions causing reduced VA were explored and those with treatable conditions allowing visual improvement identified. Duration since last optometry review was recorded. Associations were explored using unpaired t -tests for continuous and chi-squared for discrete variables. Logistic regression was used for multivariate analysis and to determine odd ratios in the final adjusted model. Statistical analysis was performed using Stata 14.0 (Stata Corp, Tx). Within this sample, 7.1% (95% CI 6.0–8.3) of drivers fell below the VA legal driving standard (6/12) in their better eye, with 20% not having seen an optometrist for 2 years, including 8.2% who had not attended for over 5 years. The percentage of drivers falling below the VA minimum increases with age reaching 22.8% (95% CI 13.7–35.3) among those aged 85–89 years. 7.2% (95% CI 6.2–8.6) of drivers had bilateral visual field defects. 93% of drivers with reduced VA below legal standard had a cataract, refractive error or both in at least one eye. Significant numbers of elderly drive with VA below legal standard, most having easily correctable causes. Poor attendance with optometrists appears commonplace. Public education raised awareness of legal driving standards and encouraged compliance are required. Regular eye tests, appropriate refractive correction, and cataract surgery when needed should be encouraged.